(untitled) (Research, Society and Development, 2021)
This article aims to discuss work as an educational principle from the perspective of Professional and Technological Education. This is an approach to the evolution of the educational identity of work in light of the marketing sense historically acquired through the process of capitalist development, as well as on education and its transformations throughout history, analyzing its changes and highlighting the unveiling of the project. current Brazilian educational This work is a qualitative research, through a descriptive and bibliographical study, based on theorists who study the subject, among others that contemplate the theme. The results of this research reveal that it is necessary to understand the two sides of work, both in the ontological and in the historical sense, for the entire problematic of the conception of work in professional education. The study concludes that it is necessary to consider dialectics and as contradictions immanent to the historical development of human sociability, conditions of possibility for the construction of a more just and humane society project, thought beyond the market, as focusing on work as an educational principle as a concept to be adopted in Professional and Technological Education.